2019
DOI: 10.28920/dhm49.2.88-95
|View full text |Cite
|
Sign up to set email alerts
|

Serum tau concentration after diving – an observational pilot study

Abstract: Increased concentrations of tau protein are associated with medical conditions involving the central nervous system, such as Alzheimer's disease, traumatic brain injury and hypoxia. Diving, by way of an elevated ambient pressure, can affect the nervous system, however it is not known whether it causes a rise in tau protein levels in serum. A prospective observational pilot study was performed to investigate changes in tau protein concentrations in serum after diving and also determine their relationship, if an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…The results from this study contrasted with results from a small pilot study on 10 divers, where tau concentration had increased significantly, but NfL and GFAp concentrations were unchanged after repeated diving during four days to at most between 52 and 90 m (Rosén 2019 ). However, hyperbaric exposure to 401 kPa followed by slow decompression is a qualitatively different exposure compared to repeated and deep diving and the results could be consistent with each other.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results from this study contrasted with results from a small pilot study on 10 divers, where tau concentration had increased significantly, but NfL and GFAp concentrations were unchanged after repeated diving during four days to at most between 52 and 90 m (Rosén 2019 ). However, hyperbaric exposure to 401 kPa followed by slow decompression is a qualitatively different exposure compared to repeated and deep diving and the results could be consistent with each other.…”
Section: Discussioncontrasting
confidence: 99%
“…Increased levels of tau have been reported in the context of dementia, brain injury (Zetterberg 2016 , Mattson 2017 ), cerebral concussion (Shahim 2014 , Zetterberg 2016 ) and boxing (Neselius 2012 , Zetterberg 2006 ), but also after less evident neuronal trauma as protracted apnea (Gren 2016 ) and uneventful anaesthesia (Evered 2018 ). A small pilot study found elevated tau levels in blood after diving (Rosén 2019 ). However, another small pilot study found no increase in tau levels in cerebrospinal fluid among divers with DCS (Shahim 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies corroborated by epidemiological evidence in neurodegenerative diseases have suggested a role that sex may play in modulating the release of tau, a neuroaxonal injury marker, into biofluids while interacting with disease development and progression ( 10 – 12 ). Moreover, the use of an ultra-sensitive assay—single molecule array (SIMOA) technology—has consistently demonstrated the feasibility and reliability of detecting substantially low concentrations of total-tau (t-tau) in blood, making possible its accurate longitudinal measurement in athletes ( 5 , 13 15 ). Thus, the current work investigated the potential influence of sex in the expression and release of t-tau ( 16 ), following sports-related concussion.…”
Section: Introductionmentioning
confidence: 99%
“…Trimix breathing gas is used for deep dives and contains oxygen, helium and nitrogen. Tau increased by 98.8% in a small pilot study where ten divers performed repeated deep dives between 52–90 msw over 4 days using trimix (Rosén et al 2019 ), with an oxygen partial pressure of 130 kPa during the dive and up to 160 kPa during decompression; nitrogen pressures at depth were around 176–193 kPa. In the present study the partial pressures of oxygen and nitrogen at depth were 109 kPa and 406 kPa, respectively.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Physiological stressors such as protracted apnea among breath-hold divers (Gren et al 2016 ) and high intensity interval training (Battista et al 2018 ) have both been associated with increased tau levels in blood. A small pilot study found increased serum tau levels in blood after repeated deep, open sea diving (Rosén et al 2019 ). In contrast, tau levels were not increased in cerebrospinal fluid in a small study on divers with DCS, though only one of seven patients in the study had CNS symptoms (Shahim et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%